p19Arf suppresses growth, progression, and metastasis of Hras-driven carcinomas through p53-dependent and -independent pathways. - Karen S Kelly-Spratt; Kay E Gurley; Yutaka Yasui; Christopher J Kemp (PLoS Biology)
Ectopic expression of oncogenes such as Ras induces expression of p19(Arf), which, in turn, activates p53 and growth arrest. Here, we used a multistage model of squamous cell carcinoma development to investigate the functional interactions between Ras, p19(Arf), and p53 during tumor progression in the mouse. Skin tumors were induced in wild-type, p19(Arf)-deficient, and p53-deficient mice using the DMBA/TPA two-step protocol. Activating mutations in Hras were detected in all papillomas and carcinomas examined, regardless of genotype. Relative to wild-type mice, the growth rate of papillomas was greater in p19(Arf)-deficient mice, and reduced in p53-deficient mice. Malignant conversion of papillomas to squamous cell carcinomas, as well as metastasis to lymph nodes and lungs, was markedly accelerated in both p19 (Arf)- and p53-deficient mice. Thus, p19(Arf) inhibits the growth rate of tumors in a p53-independent manner. Through its regulation of p53, p19(Arf) also suppresses malignant conversion and metastasis. p53 expression was upregulated in papillomas from wild-type but not p19( Arf)-null mice, and p53 mutations were more frequently seen in wild-type than in p19( Arf)-null carcinomas. This indicates that selection for p53 mutations is a direct result of signaling from the initiating oncogenic lesion, Hras, acting through p19(Arf).